Electrocatalysis of Formate Dehydrogenase Towards CO2 Reduction - Baptista, Rita Helena Duarte (2022)
The continuous strong growth of CO2 emissions and the intensification of environmental impacts caused by this gas have aroused an increasing interest in the development of strategies to transform CO2. Formate dehydrogenases (FDH) are enzymes that perform the reversible interconversion of formate to CO2, hence these biocatalysts can transform CO2 into a compound that can be used either as a biofuel or as chemical precursor for sustainable chemical synthesis. Reports on direct electrochemical approaches, avoiding kinetic limitations of the mediating molecules and additional steps of cofactors regeneration, have been scarce until recently. In this Thesis, the electrochemical characterisation of the molybdenum-containing FDH from Desulfovibrio desulfuricans (DdFDH) was accomplished through non-mediated methods, in the absence of added substrates (non-turnover conditions), for the enzyme physically adsorbed onto a pyrolytic graphite electrode, at pH 6.5. A redox process with formal potential of -124 ± 11 mV vs NHE was assigned to the redox pair Mo (VI/IV) of the active centre. The heterogeneous electron transfer rate constant increased with the scan rate, which is indicative of a good communication between the enzyme and the electrode. The DdFDH catalytic response towards CO2 reduction was attained without mediators as well, upon the addition of saturated CO2 solution and sodium carbonate solution for the DdFDH adsorbed onto a stationary pyrolytic graphite electrode. The electrocatalysis towards CO2 reduction was also attained for DdFDH physically adsorbed on glassy carbon and graphite, under the hydrodynamic regime, and for the DdFDH encapsulated on felt carbon, a gas diffusion electrode.